THE SUGAR BUSH- MAPLE SYRUP - Chatterjee, Bandana (International Journal of Clinical and Biomedical Research, 2016)
Maple syrup is the syrup made from the xylem sap of trees like sugar maple, red maple, black maple and some other maple species. From one of nature’s true phenomena the process of maple syrup production gets started. During spring when the nights are very cold, the maple tree absorbs water from the soil. In the daytime due to warmer temperature a pressure is created which pushes the water again to the tree bottom which helps in easy collection of the maple syrup which is very precious actually. It takes almost 12 to 20 days to collect the sap depending on the area / region. KEYWORDS: Maple syrup; Spring, Warmer temperature.